1998
DOI: 10.1161/01.cir.98.16.1657
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Cell Proliferation After Porcine Coronary Angioplasty

Abstract: These results suggest that the profile of apoptosis and proliferation after PTCA is regional and cell specific, and attempts to modulate either of these events for therapeutic benefit requires recognition of these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
84
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 30 publications
8
84
0
Order By: Relevance
“…Apoptosis has been described in both neointima, media and adventitia 39,40 with a maximum in neointima and media between 7 and 14 days after surgery 40 We demonstrate here that apoptosis was present at 7 days in Ad-␤Gal-infected arteries and was prevented by infusion of Ad-S2a.…”
Section: Discussionmentioning
confidence: 49%
“…Apoptosis has been described in both neointima, media and adventitia 39,40 with a maximum in neointima and media between 7 and 14 days after surgery 40 We demonstrate here that apoptosis was present at 7 days in Ad-␤Gal-infected arteries and was prevented by infusion of Ad-S2a.…”
Section: Discussionmentioning
confidence: 49%
“…In contrast, chlamydial induction of foam cell formation, for example, can be promoted by chlamydial LPS alone (26). Proliferation of vascular cells has been characterized earlier as an integral part of atherosclerosis (27) and represents a general mechanism of arterial injury as observed in neointima formation after coronary angioplasty (28). The effects seen cannot be regarded as specific for C. pneumoniae or even bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inhibitory effect of RIP3 overexpression on neointimal formation is likely attributable to the increased apoptosis as well as suppressed proliferation of VSMCs. But it is still a matter of debate as to what is the impact of VSMC apoptosis on neointimal formation, as some evidence suggests that early apoptosis of medial VSMCs may increase late neointimal formation in vivo (53). Our preliminary data have demonstrated that overexpression of rRIP3 overtly attenuates VSMC migration (data not shown).…”
Section: Discussionmentioning
confidence: 79%